MODIFICATION OF THE SURFACE OF CARBON BLACK WITH VINYL ETHER COPOLYMERS UNDER ULTRASONIC TREATMENT - Aleksandrova, Yulia; Budanova, Natalia; Zharova, Nelli; Okorokova, Nadezhda; Ustyuzhaninova, Galina; Farmakovskaya, Ariadna; Kohlert, Victoria (Revista Inclusiones, 2020)
In this work, we investigated the possibility of stabilizing aqueous dispersed carbon systems with vinyl ether copolymers. It was shown that the presence of hydrophobic fragments in the macromolecule chain plays a significant role and positively affects the results of stabilization of aqueous dispersions of carbon particles. Studies have shown that the use of a stabilizer in combination with ultrasonic treatment of dispersed systems allows obtaining stable homogeneous highly dispersed suspensions. It was noted that a strong increase in the time and intensity of ultrasound processing of the system does not lead to a significant improvement in the results.